Superovulation and embryo transfer in Bos indices cattle - Baruselli, P. S.; de Sa, M. F.; Martins, C. M.; Nasser, L. F.; Nogueira, MFG; Barros, C. M.; Bo, G. A. (Elsevier B.V., 2006)
Compared to Bos taurus breeds, Bos indices breeds of cattle present several differences in reproductive physiology. Follicular diameter at deviation and at the time of ovulatory capability are smaller in B. indicus breeds. Furthermore, B. indicus breeds have a greater sensitivity to gonadotropins, a shorter duration of estrus, and more often express estrus during the night. These differences must be considered when setting up embryo transfer programs for B. indicus cattle. In recent studies, we evaluated follicular dynamics and superovulatory responses in B. indicus donors with the objective of implementing fixed-time AI protocols in superstimulated donors. Protocols using estradiol and progesterone/progestrogen releasing devices to control follicular wave emergence were as efficacious as in B. taurus cattle, allowing the initiation of superstimulatory treatments (with lower dosages of FSH than in B. taurus donors) at a self-appointed time. Furthermore, results presented herein indicate that delaying the removal of progesterone/progestogen-releasing devices, combined with the administration of GnRH or pLH 12 h after the last FSH injection, results in synchronous ovulations, permitting the application of fixed-time AI of donors without the necessity of estrus detection and without compromising the results. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: superstimulation; embryo transfer; Bos indices; fixed-time AI; ultrasonography